EFL University Students' Reading Strategy Use across Personality Types in Understanding English Online Texts - Merliyani Putri Anggraini; Bambang Yudi Cahyono; Mirjam Anugerahwati; Francisca Maria Ivone (English Language and Literature International Conference (ELLiC) Proceedings, 2022)
Reading strategies are the crucial factors in determining the success of reading comprehension, moreover in an online environment. However, previous research moderating participants' personalities in determining the reading strategy use is still inconclusive. This study aimed to explore the reading strategies used by EFL university students across personality types in understanding English online texts, and to examine the relationship between personality types and reading strategies. A quantitative study was administered to answer the research questions using a survey of online reading strategies (SORS). The research participants included 248 second-year university students in one of the universities in Indonesia. They were asked to attend the personality test to know whether they were extroverts or introverts. The findings revealed that extroverted students tended to use socio-affective strategies. Meanwhile, introverted students preferred to use global strategies. Interestingly, both types of students were noticed to employ support reading strategies occasionally. The significant but weak relationship between personality types and strategy use was merely found in global and socio-affective strategies. The results suggest that teachers in online reading classes should train their students to use various reading strategies so that the students with extroverted or introverted personalities can maximize their online reading comprehension